Evaluation Of Particulate Matter (PM2.5 And PM10) And Falling Dust Levels And Their Relationship To Some Climatic Factors In Selected Areas In Anbar Governorate (International Journal of Environmental Sciences, 2025)
Fine particulate matter (PM2.5 and PM10) is one of the most impactful air pollutants on human health and the environment, especially in industrial areas. This study aims to assess these particles and falling dust from several selected locations in Anbar Governorate. The study relied on field readings from 21 fine particulate matter monitoring stations (10 industrial stations, 6 residential stations, 4 commercial stations, and 1 control station), in addition to 16 dust monitoring stations (6 industrial stations, 6 residential stations, and 4 commercial stations), along with measurements of some climatic factors such as temperature, relative humidity, and wind speed. Data were collected from environmental monitoring stations over a period of four months (October, January, March, and April) using precision instruments.The study results revealed significant variations in pollution levels at the stations selected for the study. The highest concentrations of suspended particulate matter (PM10) were recorded at (200, 117, and 88) micrograms/m3 in the industrial, commercial, and residential areas, respectively. The results confirmed that all industrial stations recorded concentrations higher than the global and local permissible limits, while none of the residential stations exceeded these limits. The results indicated that PM2.5 recorded the highest concentrations at (58, 42, and 32) micrograms/m3 in the industrial, commercial, and residential areas, respectively. The industrial and commercial areas exceeded the global and national limits (except for the commercial A10 in Haditha), while the residential stations did not exceed these limits. The results also showed that the concentrations of particulate matter (PM10 and PM2.5) recorded at the stations selected for the study were higher when compared to the monitoring (control) station.The study results also showed that the Kubisa Cement Plant recorded the highest levels of falling dust, at 834.78 g/m²/month, in April.The study also demonstrated statistically significant correlations between some climatic factors and suspended particulate matter concentrations, with particulate matter concentrations (PM2.5, PM10) showing an inverse relationship with wind speed and temperature, and a direct relationship with relative humidity. However, no climatic factor was statistically significantly associated with falling dust.